PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN - Asfira, Asfira; Rijal, Abdul; Hamzah, Hajrah (LPPM Universitas Bina Bangsa, 2024)
This research aims to analyze to analyze the influence of taxpayer awareness and tax knowledge towards Taxpayer Compliance in Paying Land and Building Taxes in East Tonrokassi Village, Tamalatea District, Jeneponto Regency. The population in this research is land and building tax payers in East Tonrokassi Village, Tamalatea District, Jeneponto Regency. The population in this study was 2698 Taxpayers. while the sample was 97 taxpayers taken using a non-probability sampling technique using a purposive sampling method. Data collection was carried out using questionnaires. The data analysis used is instrument testing, classical assumption testing, and hypothesis testing using SPSS v. 25 for windows. The results of this research show that Taxpayer Awareness and Tax Knowledge influence taxpayer compliance in paying Land and Building Tax in East Tonrokassi Village, Tamalatea District, Jeneponto Regency